Re-irradiation in recurrent malignant glioma: prognostic value of [18F]FET-PET - Niyazi, Karim-Maximilian; Büsing, Karen-Anett (Journal of neuro-oncology, 2012)
The aim of the present study is to determine new positron emission tomography (PET) imaging-related factors predictive of progression-free survival as well as survival in patients with recurrent malignant glioma (MG) prior to and after re-irradiation. Fifty-six patients with recurrent MG who underwent re-irradiation treatment and pretherapeutic dynamic [18F]-fluoroethyl-l-tyrosine (FET)-PET scan were retrospectively analyzed. The prognostic value of different parameters, such as biological tumor volume, maximal tumor uptake (SUVmax/BG), mean tumor uptake (SUVmean/BG), as well as uptake kinetics, was evaluated. [18F]FET uptake kinetics was classified according to a five-point rating as category G1-2 (strongly/mainly increasing kinetics), G3 (mixed 1:1), or G4-5 (mainly/strongly decreasing kinetics). Patients within the pretherapeutic kinetic group G4-5 had significantly worse survival than the other two groups (p = 0.01). Multivariate analysis revealed that histologic grade, Karnofsky Performance Score (KPS), and kinetic group were independent significant predictors for survival after re-irradiation. The uptake kinetics of [18F]FET-PET is an independent determinant of overall and to a lesser extent also progression-free survival. Thus, [18F]FET-PET kinetics may provide valuable additional prognostic information for treatment decisions.
Gesehen am 16.08.2018
Im Titel ist "18" in [18F]FET-PET hochgestellt